Profile Evaluation of Medication, Cost Comparison, and Clinical Outcome of Human and Analog Insulin Treatment to Type-2 Diabetes Mellitus Outpatient at Medistra Hospital Year 2012-2013 - Elisabeth Ninung Yuliarti; Yusi Anggriani; Dian Ratih Laksmitawati; Prasasta Sutedjo (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
The data collection was conducted retrospectively, taking samples of 121 outpatients, of which 83 outpatients were evaluated for their clinical outcome. The medication profile data were collected from the medicine administration at the Hospital Pharmacy Installation. The clinical outcome data, such as fasting plasma glucose (FPG), two-hour postprandial plasma glucose (2HPP), and Hemoglobin A1c (HbA1c), were garnered from the patients’ medical records. The cost data were collected from the outpatients’ payment receipts provided by the Hospital’s Financial Department. Kolmogorov Smirnov normality test was applied in this research. The research result suggests that after Mann Whitney Test, the human and analogue insulin were not significantly different seen from the clinical outcome result showing FPG (p=0.676), 2HPP (p=0.175), HbA1c (p=0.0445) and from the cost result (p=0.795). Furthermore, the research also shows that the average cost of 30-day medication of single human insulin was Rp3,190,997.43, while the one of analogue insulin was Rp3,188,832.35. In conclusion, the research finds out that if seen from the cost (p=0.795), the human and the analogue insulin were not significantly different.